Youth political dependency in social media and its influence on the Kajang state assembly in Selangor - Mohd, Mohd Ezril; Ku Sansu, Ku Hasnita; Ahmad, Nobaya (Institute for Youth Research Malaysia, 2019)
This research paper discusses the influence of political socialization dependency in social media, especially among the youth that may cause changes in their political culture, especially in Kajang State Assembly (DUN Kajang), Selangor. The internet political campaigns can be seen since the 12th general election (GE-12) when it managed to influence the voters and led to the failure of the Barisan Nasional (BN) to retain their over 50 years of majority of two-thirds of parliamentary seats. This development has been linked to the critical attitude taken by the youth towards the Federal Government due to their over-dependence to political information in social media which is believed to be dominated by the pro-opposition. Thus, the main objective of the study is to examine the relationship between political socialization dependency in social media and political culture change among the urban youth; while analysing in detail which demographic factors that may influence it. Cluster random sampling method was used involving 432 respondents in DUN Kajang. Statistical Package for Social Science (SPSS v23) has been used for descriptive statistics analysis such as frequency, percentage and mean score, along with Pearson correlation, linear regression and ANOVA analysis particularly in determining differences and identifying relationship between the variables. In general, the findings show that youth political dependency in social media for political purposes has negative, but weak and statistically non-significant relationship with political culture change. However, ethnic factor has been proven to significantly influence the political culture change. Variables such as political socialization dependency in social media and political culture change are basically correlated to each other. Hence, the next step for future research is to further compare the effects of political socialization dependency in social media among the urban and rural youths, so that accurate generalisation can be deduced.